Effect of central serous chorioretinopathy patients by covering sick eye for 48 hours - Zhao,Hongwei (2021)
ABSTRACT Purpose: To assess the effect of continuously covering the sick eye affected with central serous chorioretinopathy for 48 h. Methods: This retrospective, case-control study involved 32 central serous chorioretinopathy patients categorized in the treatment group composed of 17 sick eye that received continuous covering treatment for 48 h with a medical gauze and the observation group composed of 15 of these patients who were followed up. None of the patients received any other treatments or medications. The logarithm of the minimal angle of resolution (logMAR) best-corrected visual acuity, macular retinal thickness, and the root mean square value of the amplitude density in the first ring of multifocal electroretinogram were examined before and after the 48-h treatment. Results: After the continuous treatment, the logMAR best-corrected visual acuities were 0.31 ± 0.18 and 0.56 ± 0.37 in the treatment and observation groups, respectively (p=0.019). The macular retinal thicknesses were 461 ± 43 µm and 498 ± 50 µm in the treatment and observation groups, respectively (p=0.032). The root mean square values of the amplitude density in the first ring of multifocal electroretinogram were 32.5 ± 5.3 nV/deg2 and 26.6 ± 4.3 nV/deg2 in the treatment and observation groups, respectively (p=0.002). Conclusions: The continuous application of the covering treatment for 48 h on the sick eye showed positive outcomes with respect to the best-corrected visual acuity, macular retinal thickness, and macular retina functions in the treatment of central serous chorioretinopathy.